Humphrey Marshall papers - Marshall, Humphrey, 1812-1872.; McLean, John, 1785-1861.
Correspondence, diaries, speeches, writings, notes, financial and legal records, printed matter, and other papers relating chiefly to Marshall's career as a lawyer, soldier, and politician. Documents his work as a lawyer in Kentucky and Virginia and his service as U.S. representative from Kentucky, U.S. commissioner to China during the Taiping Rebellion, and U.S. army officer during the Mexican War. Subjects include the conduct of William Henry Harrison during the Battle of the Thames (1813), Kentucky state and national politics, protection of Western lives and property in China, protectionism for the hemp industry, slavery, states' rights, steam safety of river boats, trade with China, and the United States Naval Expedition to Japan (1852-1854). Subjects also include Marshall's flight from Richmond, Va., on April 2, 1865, the day the Confederate capital fell; his subsequent travels through the South; and Marshall family affairs. Collection includes an autobiography and other papers of Supreme Court Justice John McLean; a letter of Patrick Henry to George Rogers Clark; and a Virginia land grant issued by Henry while governor. Many of the items in the collection include notes and emendations by the donor, William E. McLaughry. Correspondents include John H. Aulick, John J. Crittenden, Jefferson Davis, Millard Fillmore, Walter Newman Haldeman, Isham G. Harris, George Law, John McLean, Matthew Calbraith Perry, William B. Reed, Alexander Hamilton Stephens, Bayard Taylor, and Daniel Webster.
Chiefly photocopies.
Army officer, lawyer, U.S. representative from Kentucky, and C.S.A. representative from Virginia.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
One letter (1867) was previously cataloged separately as part of the Miscellaneous Manuscripts collection.
Keywords: Aulick, John H., -- -1873 -- Correspondence; Clark, George Rogers, -- 1752-1818 -- Correspondence; Crittenden, John J. -- 1787-1863 -- Correspondence; Davis, Jefferson, -- 1808-1889 -- Correspondence; Fillmore, Millard, -- 1800-1874 -- Correspondence; Haldeman, Walter Newman, -- 1821-1902 -- Correspondence; Harris, Isham G. -- 1818-1897 -- Correspondence; Harrison, William Henry, -- 1773-1841.; Henry, Patrick, -- 1736-1799 -- Correspondence; Law, George, -- 1806-1881 -- Correspondence; McLaughry, William E; McLean, John, -- 1785-1861 -- Correspondence; Perry, Matthew Calbraith, -- 1794-1858 -- Correspondence; Reed, William B. -- 1806-1876 -- Correspondence; Stephens, Alexander Hamilton, -- 1812-1883 -- Correspondence; Taylor, Bayard, -- 1825-1878 -- Correspondence; Webster, Daniel, -- 1782-1852 -- Correspondence; Marshall family; Americans -- China; Diplomatic and consular service, American; Europeans -- China; Hemp industry; Land grants -- Virginia; Mexican War, 1846-1848.; Practice of law -- Kentucky; Practice of law -- Virginia; Protectionism -- United States; River boats; Slavery; States' rights (American politics); Thames, Battle of the, Ont., 1813.; China -- Commerce -- United States; China -- Foreign relations -- United States; China -- History -- Taiping Rebellion, 1850-1864.; Japan -- Description and travel; Kentucky -- Politics and government; Richmond (Va.) -- History -- Civil War, 1861-1865.; Southern States -- Description and travel; United States -- Commerce -- China; United States -- Foreign relations -- China; United States -- History -- War of 1812 -- Campaigns; United States -- History -- Civil War, 1861-1865.; United States -- Politics and government -- 1849-1877.; Virginia -- History -- Civil War, 1861-1865.; Army officers; Lawyers; Representatives, C.S.A. Congress -- Virginia; Representatives, U.S. Congress -- Kentucky